Sharing economy as a remedy for Covid-19 crisis - Iwona LUPA-WOJCIK (Communications of International Proceedings, 2021)
The sharing economy is a trend that has been systematically developing for years. Its main development factors, apart from the Internet and social media, include crises. The sharing economy ensures that all consumers in the market can use goods and services on the market, even those who have been hit by the crisis, while minimizing the discomfort of those who are doing better at the time. The purpose of this article is to discuss the issue of the sharing economy as a remedy for the Covid-19 crisis. The main hypothesis states that Covid-19 crisis stimulated development of sharing economy. As a research method was used the analysis of documents, including reports and statistics on the development of the sharing economy. The analysis showed that despite the Covid-19 crisis, sharing economy transactions are developing dynamically, making it possible to meet the needs of all consumers, including those affected by the crisis.
Keywords: sharing economy; covid-19 crisis; social media sharing